Design of a human-like biped locomotion system based on a novel mechatronic methodology. (September 2019) - Vazquez-Santacruz, JA; Torres-Figueroa, J; Portillo-Velez, R de J
In this article, a formal mechatronic design of a biped robot is addressed. It is considered a model-based system engineering methodology since the continuous updating of information, from analysis and evolution of conceptual designs, demands a large volume of data. The definition of a biped robot comes from the need of a system to perform human-like walking as the problem to be solved. A specific robot configuration results from the analysis of conceptual solutions throughout SysML as the language for modeling the synergistic and automatic integration among engineering disciplines. The general design process is developed according to the well-known V-model for mechatronic systems design; however, a three-dimensional focus is proposed in order to address a variety of domains and their interaction along the design process. The detailed study of the solution is evaluated in order to optimize the joint torques and limbs shape from an anthropometric robot to achieve effective human-like motion. Although the mechatronic design is done for the overall biped robot system, this work is particularly focused on mechanical features as the most representative subsystem that incorporates genetic algorithm optimization based on a numerical Newton–Euler model merged with topology optimization tools to define final geometry of limbs with stiffness maximization.